The Effect of Using Audio Visual Media through The Capcut Application on Writing Skills Text of Lectures for Class XI High School Students Budisatrya - Amri, Yusni Khairul; Azizah, Nur (Talenta Publisher, 2024)
This research aims to describe the skills in writing lecture texts by utilizing audio-visual media through the CapCut application for class The research sample consisted of students from class XI IPA 1 as an experimental group with a total of 30 students and class XI IPA 2 as a control group with a total of 35 students. The instrument used for data collection was a test instrument in the form of essay questions. The results of this research, in the experimental class the average value obtained was 87.53 and the average value in the control class was 77.37. Meanwhile, the results of hypothesis testing with the t-test obtained a tcount value of 6.23 with a df of 63 in ttable, so a ttable value was obtained of 1.66, thus it can be seen that tcount > ttable (6.23 > 1.66). From the results of these calculations, it can be interpreted that Ha in this study was accepted and HO was rejected, which means that there is an influence of the use of audio-visual media through the CapCut application on the lecture text writing skills of class.